Priming morfológico nos processos de leitura - Pinto, Carina (2018)
Using a masked priming paradigm we investigated the effect of a derived word prime on the recognition of a target in 3 conditions: Morphological Related Words, Ortographically Overlap Words and Unrelated Words. We tested Portuguese children in the 4th grade (N=27) and college students (N=36), using a lexical decision task. The subjects saw the rime for 50 ms. Results show differences in the word processing, both for children and adults. This indicate that morphological information exert effects in the early stages of word processing.